Dynamics of the History of the Seventh Two Kuta Kuta Hamparan Perak in Medan City, 1823-1946: Dinamika Sejarah Kedatukan Sapuluh Dua Kuta Hamparan Perak di Kota Medan, 1823-1946 - Muhammad Iqbal Roihan; Yusra Dewi Siregar (Santhet (Jurnal Sejarah Pendidikan Dan Humaniora), 2024)
This research uses historical research methods with four steps, namely heuristics, criticism, interpretation and historiography. Data is collected from archives, books, articles and reports that are relevant to the research topic. The North Sumatra Province documentation includes various references on the history, culture and society of the region, including an introduction to historical science, historical research methods, and studies of the sultanate and local culture. Some of the authors mentioned include Abdillah, Anderson, Daliman, Faruqi, Giddens, Lubis, Simanjuntak, and others. aims to explore the historical dynamics of the Kedatukan Satu Dua Kuta Hamparan Perak in Medan City from 1823-1946. The arrival of Guru Patimpus to the lowlands apparently had quite a big influence. This influence occurred in the Malay community and also the Karo community. Generally, people who want to settle in the Malay region must be converted to Islam first. The arrival of the Karo people in the lowlands was welcomed by the Malays. During the Aru Kingdom, many Karo people had settled and become residents who had converted to Islam, they married with Malay people. Marriage between Karo people who have converted to Islam or what is usually called Jawi is a common thing, not infrequently they also marry the children of Malay kings.